2018
DOI: 10.3892/mmr.2018.9216
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant club cell protein 16 (CC16) ameliorates cigarette smoke‑induced lung inflammation in a murine disease model of COPD

Abstract: Club cell protein (CC16) is expressed primarily by club cells possesses anti-inflammatory properties and is located in the bronchiolar epithelium. Previous studies have demonstrated that CC16 deficiency is associated with the progression of chronic obstructive pulmonary disease (COPD). In the present study, the therapeutic effects of recombinant rat CC16 protein in mice with COPD were examined and the underlying mechanisms investigated. A total of 30 adult male C57/BL6 mice were randomly divided into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 51 publications
(71 reference statements)
3
34
1
Order By: Relevance
“…Recently, the anti-inflammatory potential of CC16 24 h post-CLP in this model was confirmed. The local anti-inflammatory characteristic of CC16 is supported by the present data and by results previously demonstrated in non-traumatic lung injury ( 32 , 33 ). A recent study by the authors demonstrated that upon the early intratracheal neutralization of CC16 following chest trauma, reduced lung injury at 24 h post-CLP was observed ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the anti-inflammatory potential of CC16 24 h post-CLP in this model was confirmed. The local anti-inflammatory characteristic of CC16 is supported by the present data and by results previously demonstrated in non-traumatic lung injury ( 32 , 33 ). A recent study by the authors demonstrated that upon the early intratracheal neutralization of CC16 following chest trauma, reduced lung injury at 24 h post-CLP was observed ( 9 ).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with these studies, Pang demonstrated that recombinant rat CC16 protein inhibits LPS-induced MMP-9 expression and the production of pro-inflammatory cytokines via NF-κB pathway in model of tracheal epithelial cells and RAW264.7 macrophages [25,26]. She suggested that exogenous supplementation of recombinant CC16 ameliorates cigarette smoke-induced lung inflammation in a murine disease model of chronic obstructive pulmonary disease [27]. Further exploration is needed of CC16's function for critical care patients in the future.…”
Section: Discussionmentioning
confidence: 67%
“…As part of a family of transcription factors, NFκB increased significantly in CS-induced COPD mice. Therefore, downregulating pro-inflammatory factors via modulation of the NFκB pathway exhibited therapeutic effects on COPD inflammation [38][39][40]. As a pro-inflammatory cytokine, prolonged inducible nitric oxide synthase (iNOS) expression is implicated in the pathophysiology of inflammatory diseases, such as pulmonary inflammation and COPD [41,42].…”
Section: Discussionmentioning
confidence: 99%